Social differentiation and embodied dispositions: a qualitative study of maternal care-seeking behaviour for near-miss morbidity in Bolivia - Liljestrand Jerker; Jonsson Cecilia; Rööst Mattias; Essén Birgitta (BMC, 2009)
Abstract Background Use of maternal health care in low-income countries has been associated with several socioeconomic and demographic factors, although contextual analyses of the latter have been few. A previous study showed that 75% of women with severe obstetric morbidity (near-miss) identified at hospitals in La Paz, Bolivia were in critical conditions upon arrival, underscoring the significance of pre-hospital barriers also in this setting with free and accessible maternal health care. The present study explores how health care-seeking behaviour for near-miss morbidity is conditioned in La Paz, Bolivia. Methods Thematic interviews with 30 women with a near-miss event upon arrival at hospital. Near-miss was defined based on clinical and management criteria. Modified analytic induction was applied in the analysis that was further influenced by theoretical views that care-seeking behaviour is formed by predisposing characteristics, enabling factors, and perceived need, as well as by socially shaped habitual behaviours. Results The self-perception of being fundamentally separated from "others", meaning those who utilise health care, was typical for women who customarily delivered at home and who delayed seeking medical assistance for obstetric emergencies. Other explanations given by these women were distrust of authority, mistreatment by staff, such as not being kept informed about their condition or the course of their treatment, all of which reinforced their dissociation from the health-care system. Conclusion The findings illustrate health care-seeking behaviour as a practise that is substantially conditioned by social differentiation. Social marginalization and the role health institutions play in shaping care-seeking behaviour have been de-emphasised by focusing solely on endogenous cultural factors in Bolivia.